Type 2 diabetes mellitus and sepsis: state of the art, certainties and missing evidence - Costantini, Elisa (Acta Diabetol, 2021)
Diabetes and sepsis are important causes of morbidity and mortality worldwide, and diabetic patients represent the largest population experiencing post-sepsis complications and rising mortality. Dysregulated immune pathways commonly found in both sepsis and diabetes contribute to worsen the host response in diabetic patients with sepsis. The impact of diabetes on mortality from sepsis is still controversial. Whereas a substantial proportion of severe infections can be attributed to poor glycemic control, treatment with insulin, metformin and thiazolidinediones may be associated with lower incidence and mortality for sepsis. It has been suggested that chronic exposure to high glucose might enhance immune adaptation, leading to reduced mortality rate in septic diabetic patients. On the other hand, higher risk of acute kidney injury has been extensively documented and a suggested lower risk of acute respiratory distress syndrome has been recently questioned. Additional investigations are ongoing to confirm the protective role of some anti-diabetic treatments, the occurrence of acute organ dysfunction, and the risk/benefit of less stringent glycemic control in diabetic patients experiencing sepsis. Based on a MEDLINE/PubMed search from inception to December 31, 2020, the aim of this review is therefore to summarize the strengths and weaknesses of current knowledge on the interplay between diabetes and sepsis.